Persistent deep-water formation in the Nordic Seas during Marine Isotope Stages 5 and 4 notwithstanding changes in Atlantic overturning - T. B. Stobbe; H. A. Bauch; H. A. Bauch; D. A. Frick; J. Yu; J. Gottschalk (Climate of the Past)
Alongside shifts in Pacific and Southern Ocean carbon cycling, reductions in the extent and formation of North Atlantic Deep Water (NADW) and the expansion of southern sourced waters in the Atlantic Ocean were linked to enhanced marine carbon storage during glacial periods and are considered key mechanisms explaining late Pleistocene atmospheric CO2 variations on glacial–interglacial timescales. However, changes in the formation of deep waters in the Nordic Seas, an important source of NADW, and their influence on the geometry and intensity of Atlantic overturning remain poorly understood, especially beyond the last glacial maximum, leaving possible impacts on atmospheric CO2 changes elusive. Here, we present high-resolution Cibicidoides wuellerstorfi B /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="e653eaf840568ee76bb20ba3bf368ae0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-1281-2025-ie00001.svg" width="8pt" height="14pt" src="cp-21-1281-2025-ie00001.png"/></svg:svg> Ca-based bottom water [CO<msubsup>32-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="490d7ecf09fa5682b13318d48526c23f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-1281-2025-ie00002.svg" width="13pt" height="17pt" src="cp-21-1281-2025-ie00002.png"/></svg:svg>] reconstructions, alongside complementary C. wuellerstorfi stable oxygen and carbon isotopes and abundance estimates of aragonitic pteropods in marine sediment core PS1243 from the deep Norwegian Sea to investigate past deep-water dynamics in the Nordic Seas and potential impacts on Atlantic overturning and carbon cycling. Our data suggest continuous formation of dense and well-ventilated (high [CO<msubsup>32-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="a6bb0ebeb981e933bf20c4403fdee544"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-1281-2025-ie00003.svg" width="13pt" height="17pt" src="cp-21-1281-2025-ie00003.png"/></svg:svg>]) deep waters throughout Marine Isotope Stages (MIS) 5 and 4, alongside a deepening of the aragonite compensation depth by at least 700 m between MIS 5b and MIS 4 (91–57 ka before present), consistent with sustained Nordic Seas convection. In addition, slightly higher, yet statistically significant, mean bottom water [CO<msubsup>32-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="9411d275d249c3156a68c941c291c1e9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-1281-2025-ie00004.svg" width="13pt" height="17pt" src="cp-21-1281-2025-ie00004.png"/></svg:svg>] during MIS 5e (sensu stricto, 126–116 ka before present) compared to the Holocene (last 10 ka) highlights the resilience of Nordic Seas overturning towards a warmer North Atlantic, decreased Arctic sea ice extent and meltwater supply from surrounding ice sheets, although centennial-scale perturbations cannot be excluded. A compilation of bottom water [CO<msubsup>32-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="be2ac69e430c1b4dbf854d6ec9df03d4"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-1281-2025-ie00005.svg" width="13pt" height="17pt" src="cp-21-1281-2025-ie00005.png"/></svg:svg>] records from the Atlantic Ocean indicates that dense waters from the Nordic Seas may have continuously expanded into the intermediate and/or deep (western) North Atlantic via supply of dense-water overflows across the Greenland–Scotland Ridge, diminishing the capacity of the North Atlantic to store carbon during MIS 4. Our study emphasises differences in the sensitivity of North Atlantic and Nordic Seas overturning dynamics to climate boundary conditions of the last glacial cycle that have implications for the carbon storage capacity of the Atlantic Ocean and its role in atmospheric CO2 variations.